Human mesenchymal stem cells differentiate into an osteogenic lineage in presence of strontium containing bioactive glass nanoparticles - Parichart,N; Tsigkou,O; Li,S; Porter,A; Jones,J (Acta Biomaterialia, 2019)
While bioactive glass and ions released during its dissolution are known to stimulate osteoblast cells, the effect bioactive glass has on human stem cells is not clear. Here, we show that spherical monodispersed strontium containing bioactive nanoparticles (Sr-BGNPs) of composition 90.6 mol% SiO2, 5.0 mol% CaO, 4.4% mol% SrO (4.4%Sr-BGNPs) and 88.8 mol% SiO2, 1.8 mol% CaO, and 9.4 mol% SrO (9.4%Sr-BGNPs) stimulate bone marrow derived human stem cell (hMSC) differentiation down an osteogenic pathway without osteogenic supplements. The particles were synthesised using a modified Stber process and had diameters of 90 ± 10 nm. Previous work on similar particles that did not contain Sr (80 mol% SiO2, 20 mol% CaO) showed stem cells did not differentiate when exposed to the particles. Here, both compositions of the Sr-BGNPs (up to concentration of 250 μg/mL) stimulated the early-, mid-, and late-stage markers of osteogenic differentiation and accelerated mineralisation in the absence of osteogenic supplements. Sr ions play a key role in osteogenic stem cell differentiation. Sr-BGNP dissolution products did not adversely affect hMSC viability and no significant differences in viability were measured between each particle composition. Confocal and transmission electron microscopy (TEM) demonstrated that monodispersed Sr- BGNPs were internalised and localised within vesicles in the cytoplasm of hMSCs. Degradation of particles inside the cells was observed, whilst maintaining effective cations (Ca and Sr) in their silica network after 24 h in culture. The uptake of Sr-BGNPs by hMSCs was reduced by inhibitors of specific routes of endocytosis, indicating that the Sr-BGNPs uptake by hMSCs was probably via mixed endocytosis mechanisms. Sr-BGNPs have potential as injectable therapeutic devices for bone regeneration or treatment of conditions such as osteoporosis, because of their ability deliver a sustained release of osteogenic inorganic cations, e.g. calcium (Ca) or a